2018
DOI: 10.1186/s12931-018-0958-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of outdoor air pollutants on outpatient visits for respiratory diseases during 2012–2016 in Jinan, China

Abstract: BackgroundFew studies have investigated the associations between outdoor air pollution and outpatient visits for respiratory diseases (RDs) in general population.MethodsWe collected daily outpatient data of primary RDs from five hospitals in Jinan during January 2012 and December 2016, as well as daily measurements of air pollutants from the Jinan Environmental Monitoring Center and daily meteorological variables from the China Meteorological Data Sharing Service System. A generalized additive model (GAM) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…However, there is lack of consistent results for sex differences in health effects of various air pollutants. Many similar studies conducted in Beijing for asthma children [43], in Ningbo for respiratory infections children [44], in Jinan for outpatient respiratory diseases [45] and in Hanoi for children lower respiratory infections [18] found that there was no obvious difference between boys and girls. Thus, additional studies are needed to clarify whether there are sex differences for the associations between air pollutants and respiratory diseases among children.…”
Section: Discussionmentioning
confidence: 96%
“…However, there is lack of consistent results for sex differences in health effects of various air pollutants. Many similar studies conducted in Beijing for asthma children [43], in Ningbo for respiratory infections children [44], in Jinan for outpatient respiratory diseases [45] and in Hanoi for children lower respiratory infections [18] found that there was no obvious difference between boys and girls. Thus, additional studies are needed to clarify whether there are sex differences for the associations between air pollutants and respiratory diseases among children.…”
Section: Discussionmentioning
confidence: 96%
“… 49 Another Chinese time series study of 1.4 million patient visits for respiratory diseases that included pneumonia and acute bronchitis, reported associations with higher outdoor PM 2.5 , PM 10 , NO 2 and ozone. 50 In a less-polluted part of China, PM 2.5 , PM 10 and NO 2 exposures, over the past 7 days were associated with outpatient visits for respiratory disease in a 4year period. 51 …”
Section: Discussionmentioning
confidence: 98%
“…Based on GAM, researchers find the exposure effect of PM 2.5 is significant in 2 days, 5 days and 7 days, respectively [12]. In another research, the lag effect increases from the same day and reaches a maximum on the 3rd day, and becomes insignificant after 5 days, by applying GAM in Jinan, China [13].…”
Section: Introductionmentioning
confidence: 96%